PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PUBLIK DI INDONESIA - Ferry Surya Pratama (2020)
With the changing era of the economy which was originally based on physical to non-physical, the company strives to maximize the management of its intellectual capital so that it can excel in competitive business competition. The purpose of this study was to analyze the effect of intellectual capital components with firm value and financial performance variables acting as intervening variables. Company value uses a Price to book Value (PBV) and financial performance using a proxy (ROA). The object of research used in this study is the manufacturing sector listed on the Indonesia Stock Exchange during the period 2009-2018. the sampling method uses purposive sampling so as many as 23 companies from the manufacturing sector were collected as well as data analysis using panel data regression and path analysis. The results of the research on the intellectual capita component that directly influence the value of the company are HCE and RCE, and the intellectual capital component that influences financial performance is HCE and financial performance that can mediate the relationship between the intellectual capital component to the company's value is HCE.